A Function of Form Terror Management and Structuring the Social World. [article]. - Landau, Mark J.
Drawing on lay epistemology theory (A. W. Kruglanski, 1980, 1989), the authors assessed a terror management nanlysis (J. Greenberg, S. Solomon, & Pyszczynski, 1997) of the psychological function of structuring social information. Seven studies tested variations of the hypothesis that simple, benign interpretations of social information function, in part, to manage death-related anxiety. In studies 1-4, mortality salience (MS) exaggerated primacy effects and reliance on representative information, decreased preference for a behaviorally inconsistent target among those high in personal need for structure (PNS), and increased high-PNS participants' preference for interpersonal balance. in studies 5-7, MS increased high PNS participants' preference for interpretas that suggest a just world and a benevolent causal order of events in the social world. -- (from the author)
Keywords: Psychology-Periodicals.